Pola Pertumbuhan Nannochloropsis oculata pada Kultur Skala Laboratorium, Intermediet, dan Massal [Patterns Growth Of Nannochloropsis oculata In Culture Scale Laboratory, Intermediate, and Bulk] - Abdul Manan; Indah Permata Sari (Faculty of Fisheries and Marine Universitas Airlangga, 2012)
Abstract One type of phytoplankton that are used in marine fish hatchery activities namely Nannochloropsis oculata. The purpose of study case is to know patterns growth of N. oculata in culture scale laboratory, intermediate, and bulk. Study was held in Situbondo Brackishwater Aquaculture Center of East Java in January-February 2011. Study case methods used is descriptive method. N. oculata culture techniques performed by multilevel methods, beginning with the isolation of phytoplankton in the media for/liquid, culture in test tubes 10 ml and elenmeyer 50-100 ml, culture on the bottle 100-1000 ml, culture in karboy of 20 liters, intermediate scale culture 100 - 1000 liters and a mass-scale culture with a volume of more than 1000 liters. Laboratory-scale use Walne for fertilizer. Intermediate-scale use of fertilizers FeCl3 1-2 ppm, 10 ppm EDTA, Na2HPO4 10-15 ppm, 100-150 ppm KNO3, and Tracemetals/vitmix 5 ml/m3, mass-scale culture use of fertilizers FeCl3 1 ppm, 5 ppm EDTA, TSP 20 ppm, ZA 40 ppm and 50 ppm urea. Water quality measurement results obtained by laboratory scale temperature is 23 - 25°C, intermediates and mass scale is 30°C, pH in the culture laboratory scale and intermediate is 7.7 to 7.8, mass culture pH is 7.9, salinity laboratory scale 29-30 ppt, intermediates and mass scale 30 ppt. During mass culture of N. oculata showed that the growth pattern in accordance with the general pattern of phytoplankton growth. Mass-scale culture produce 1504 x 104 cells/ml for six days.